Relation of Insulin Resistance to Longitudinal Changes in Left Ventricular Structure and Function in a General Population. Issue 7 (24th March 2018) - Cauwenberghs, Nicholas; Knez, Judita; Thijs, Lutgarde; Haddad, Francois; Vanassche, Thomas; Yang, Wen‐Yi; Wei, Fang‐Fei; Staessen, Jan A.; Kuznetsova, Tatiana
Abstract : Background: Population data on the longitudinal changes of left ventricular (LV) structure and function in relation to insulin resistance are sparse. Therefore, we assessed in a general population whether hyperinsulinemia predicts longitudinal changes in LV and arterial characteristics. Methods and Results: In 627 participants (mean age 50.7 years, 51.4% women), we assessed echocardiographic indexes of LV structure and function and carotid‐femoral pulse wave velocity by applanation tonometry at baseline and after 4.7 years. We regressed longitudinal changes in these indexes on baseline insulin and its change during follow‐up, and reported standardized effect sizes as a percentage of the SD of LV changes associated with a doubling of insulin. After adjustment, higher baseline insulin predicted a greater temporal increase in LV mass index (effect size: +15.1%) and E/e′ ratio (+22.1%), and a greater decrease in e′ peak and longitudinal strain (−11.2% to −17.1%). A greater increase in insulin during follow‐up related to a greater increase in LV mass index (+10.7%) and decline in ejection fraction and longitudinal strain (−11.4% to −15.7%). Participants who became or remained insulin resistant during follow‐up experienced worse changes in longitudinal strain, E/e′, and LV mass index as compared with participants who did not develop or had improved insulin resistance over time ( P ≤0.033). Moreover, multivariable‐adjusted increase in pulse wave velocity was higher in participants with diabetes mellitus than in participants without diabetes mellitus (+1.46 m/s versus +0.71 m/s; P =0.039). Conclusions: Hyperinsulinemia at baseline and during follow‐up predicted worsening of LV function and remodeling over time. Our findings underline the importance of management of insulin resistance.